Farmer and general public economic valuation of ecosystem services in the context of agroecological practice adoption in Western Kenya - Zander, Kerstin K.; Drucker, Adam G.; Aluso, Lillian; Mengistu, Dejene Kassahun (2024)
Agroecological practices result in the generation of both private and public ecosystem services. Furthermore, both types of services have monetary and non-monetary values associated with them and there may be trade-offs to be considered in securing the different types of services and values. With a view to assessing both the monetary and non-monetary values of the services that agroecological practices generate, a choice experiment was applied to both farmers and the general public in W Kenya. This permits an exploration of the challenges, opportunities and incentives farmers face in adopting/using agroecological practices and the value the general public (who are the ultimate beneficiaries) places on the public good ecosystem services that are generated. Recommendations related to how agroecological practices use may be facilitated in order to enhance the value of the ecosystem services they generate are subsequently drawn from the results.